2014
DOI: 10.1007/s40069-013-0047-y
|View full text |Cite
|
Sign up to set email alerts
|

On the FE Modeling of FRP-Retrofitted Beam–Column Subassemblies

Abstract: The use of fiber reinforced polymer (FRP) composites in strengthening reinforced concrete beam-column subassemblies has been scrutinised both experimentally and numerically in recent years. While a multitude of numerical models are available, and many match the experimental results reasonably well, there are not many studies that have looked at the efficiency of different finite elements in a comparative way in order to clearly identify the best practice when it comes to modelling FRP for strengthening. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…It was observed that employing a mesh size in the range of about 25-35 mm, with an aspect ratio lower than 1.5, at the critical zones where higher levels of yielding, bond-slip, and concrete damage are expected (particularly at the joint panel and the plastic hinge region), can provide sufficient accuracy. A similar suggestion could be found in the related studies (Ronagh and Baji 2014;Sagbas et al 2011;Del Vecchio et al 2015. In the other regions (outside the critical zones), the mesh size can be consistently increased (for example, up to 60 mm for JBC2).…”
Section: Fe Meshingsupporting
confidence: 87%
“…It was observed that employing a mesh size in the range of about 25-35 mm, with an aspect ratio lower than 1.5, at the critical zones where higher levels of yielding, bond-slip, and concrete damage are expected (particularly at the joint panel and the plastic hinge region), can provide sufficient accuracy. A similar suggestion could be found in the related studies (Ronagh and Baji 2014;Sagbas et al 2011;Del Vecchio et al 2015. In the other regions (outside the critical zones), the mesh size can be consistently increased (for example, up to 60 mm for JBC2).…”
Section: Fe Meshingsupporting
confidence: 87%
“…Several studies have been carried out around the world in the field of study of reinforced concrete structures in nonlinear elasticity. One can cite the studies carried out by (Islam and Shahria, 2013;Bouafia et al, 2000;Bouafia et al, 1998;Sargin, 1968;Virlogeux and M'rad, 1986;Virlogeux, 1986;Grelat and Nait rabah, 1988;Bratina, 2005), also, the calculation of reinforced concrete sections is a problem well known by several authors (Bouafia et al, 2002;Daunys and Rimovkis, 2006;Florent, 1999;Bonet et al, 2006;Choa and Kwonb, 2008;Liang and Fragomeni, 2009;Ronagh and Baji, 2014;Adjrad et al, 2016;Kachi et al, 2015;Adjrad et al, 2015). If all these studies carried out were focused on the simulation of the structural elements behavior in nonlinear elasticity, it was in an attempt to answer all the questions that have been chosen to be focused on in our research work, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Fiber-reinforced polymer (FRP) is a kind of high performance material with high strength-to-weight ratio, good durability and ease of application. The external bonding of FRP to concrete members has been accepted as an effective technology to strengthen and retrofit concrete structures (Täljsten 1996;Ronagh and Baji 2014). In FRP strengthened concrete structures, the interfacial bond between FRP and concrete is often the weakest region and can contribute to the debonding failure.…”
Section: Introductionmentioning
confidence: 99%